Taxonomy and phylogeny of Resinicium sensu lato from Asia-Pacific revealing a new genus and five new species (Hymenochaetales, Basidiomycota) - Jia Yu; Xue-Wei Wang; Shi-Liang Liu; Shan Shen; Li-Wei Zhou (IMA Fungus)
ABSTRACT Resinicium, belonging to Hymenochaetales, Agaricomycetes, is a worldwide genus of corticioid wood-inhabiting fungi. To improve the knowledge of species diversity within the Hymenochaetales, two dozen specimens from Asia-Pacific preliminarily identified to be members of Resinicium sensu lato were carefully studied from morphological and phylogenetic perspectives. From these specimens, a new monotypic genus Skvortzoviella, and five new species, viz. Resinicium austroasianum, R. lateastrocystidium, Skvortzovia dabieshanensis, S. qilianensis and Skvortzoviella lenis are described; moreover, a new basal lineage of Resinicium represented by a Vietnam specimen and three Chinese specimens of S. pinicola are identified. The six newly proposed taxa are morphologically compared with related genera and species, while the family positions of Resinicium, Skvortzovia, and Skvortzoviella within the Hymenochaetales are still ambiguous. In addition, the ancestral geographic origin of Resinicium, even though inconclusive, is now thought to be Asia-Pacific instead of tropical America as previously assumed.